2013
DOI: 10.1111/hepr.12180
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors 3, 4 and 9 in hepatocellular carcinoma: Relationship with clinicopathological characteristics and prognosis

Abstract: The results demonstrated an association between TLR3, TLR4 and TLR9 expression and tumor aggressiveness and poor prognosis in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…Conversely, expression of TLR4 on stromal fibroblasts was associated with poor prognosis in colorectal cancer14. Similar data were reported for hepatocellular carcinoma, where TLR9 expression on tumour-associated fibroblasts was associated with reduced overall survival50. Thus, our study is one of the first to experimentally demonstrate a role for radioresistant (stromal) cells in regulation of tumour progression via endosomal TLR signalling.…”
Section: Discussionsupporting
confidence: 84%
“…Conversely, expression of TLR4 on stromal fibroblasts was associated with poor prognosis in colorectal cancer14. Similar data were reported for hepatocellular carcinoma, where TLR9 expression on tumour-associated fibroblasts was associated with reduced overall survival50. Thus, our study is one of the first to experimentally demonstrate a role for radioresistant (stromal) cells in regulation of tumour progression via endosomal TLR signalling.…”
Section: Discussionsupporting
confidence: 84%
“…It is therefore of great importance to better define the function of each TLR expressed on a wide range of tumor cells. Many reports have described that HCC tumor cells from patients express TLR3 and TLR9, which are both associated with the prognosis of HCC [26]; moreover, HCC-derived cell lines are positive for both TLR3 and TLR9 [16,17,27]. Both cell-surface and cytoplasmic TLR3 expressions have been observed in HCC cells [20]; TLR9 is mainly expressed on endosomes, but cell-surface expression of TLR9 has also been observed on HCCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 24 studies1114,1838 were included in our analysis, with four of them investigated two or three TLRs synchronously. Among them, 12,1113,1826 five,13,14,2729 and eleven13,18,3038 studies focused on TLR4, TLR7, and TLR9, respectively. The flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%